2018
DOI: 10.1136/esmoopen-2018-000352
|View full text |Cite
|
Sign up to set email alerts
|

Potential new biomarkers for squamous carcinoma of the uterine cervix

Abstract: AimAn in silico pathway analysis was performed in an attempt to identify new biomarkers for cervical carcinoma.MethodsThree publicly available Affymetrix gene expression data sets (GSE5787, GSE7803, GSE9750) were retrieved, vouching for a total 9 cervical cancer cell lines, 39 normal cervical samples, 7 CIN3 samples and 111 cervical cancer samples. An Agilent data set (GSE7410; 5 normal cervical samples, 35 samples from invasive cervical cancer) was selected as a validation set. Predication analysis of microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Among these, GSE63514 and GSE9750 have been analyzed together (26,27). Other studies have also mined the GSE63514 (28) and GSE9750 (29) datasets; only the GSE7410 dataset had not yet been thoroughly examined previously, to the best of our knowledge. Therefore, the GEO2R online tool was used to perform the analyses of the three datasets to determine any potentially relevant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, GSE63514 and GSE9750 have been analyzed together (26,27). Other studies have also mined the GSE63514 (28) and GSE9750 (29) datasets; only the GSE7410 dataset had not yet been thoroughly examined previously, to the best of our knowledge. Therefore, the GEO2R online tool was used to perform the analyses of the three datasets to determine any potentially relevant factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been documented that NEK2 depeltion impairs cancer cell drug resistance through inhibition of the PP1/AKT/NF-κB signaling pathway in multiple myeloma [17,18]. Notably, a recent study reported that the mRNA expression level of NEK2 is significantly higher in invasive cervical cancer than in normal tissue [19], indicating that NEK2 may serve as a tumor-promoting protein in cervical cancer. Nevertheless, the exact roles and underlying mechanisms of NEK2 in cervical cancer progression and radioresistance has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most mild dysplastic lesions disappear spontaneously, but a significant proportion of the CIN III lesions may progress into invasive CC if left untreated [3]. These precancerous lesions have a likelihood of about 95% to be picked up in by screening programs using cytology and/or HPV testing on cervical smears [4]. They can be effectively eradicated by minimally invasive excision or ablation techniques, truly preventing CC.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades metastatic disease was treated with platinum-based chemotherapy, but there has been little improvement in the efficacy of the systemic treatment [3]. The short-lived responses to chemotherapy seen in patients with advanced cervical cancer indicate that the disease is relatively chemorefractory and up to now most new targeted drugs provided no extra survival benefit [3,4]. The Gynecologic Oncology Group (GOG) 240 phase III trial showed that addition of bevacizumab to the current golden standard (combination of topotecan-paclitaxel or cisplatin-paclitaxel) in this population is associated with a moderate increased overall survival (16.8 months vs. 13.3 months) compared to the same cytostatic combinations without antiangiogenic medication.…”
Section: Introductionmentioning
confidence: 99%